Creating and managing superior customer value - Woodside, Arch G.; Golfetto, Francesca; Gibbert, Michael (Emerald JAI, 2008)
"Superior Customer Value" (SCV) advances theory and offers new tools useful for measuring value dimensions and strength. Achieving highly useful sense making about the value concept and value metrics is important because of the substantial evidence that: customer assessments of total value in a product/service offering strongly affects acceptance and initial purchase; customer evaluations of value experiences relate strongly with retaining them and growing the share-of-business these customers award specific suppliers; and, increases in delivered-value implemented strategies relates positively to increases in profitability. "SCV" focuses on advancing value theory, research, and strategy in business-to-business contexts. Coverage includes in-depth case research findings for existing and disruptively new products and services and all papers in this volume embrace the proposition that context is a major force affecting planning and implementing strategy. "SCV" is relevant in particular to European and North American B-to-B contexts. However, the tools and theories in the volume are certainly relevant for research by scholars and decisions by executives working in Asia and Australia. "SCV" is essential reading for improving thinking, decisions, and actions relating to the creation, marketing, and purchasing of superior value in products and services - critical abilities for product-service executives.
Keywords: Customer relations -- Management.; Relationship marketing.; elektronické knihy; electronic books